2019
DOI: 10.7717/peerj.6650
|View full text |Cite
|
Sign up to set email alerts
|

Using road patrol data to identify factors associated with carnivore roadkill counts

Abstract: As the global road network expands, roads pose an emerging threat to wildlife populations. One way in which roads can affect wildlife is wildlife-vehicle collisions, which can be a significant cause of mortality through roadkill. In order to successfully mitigate these problems, it is vital to understand the factors that can explain the distribution of roadkill. Collecting the data required to enable this can be expensive and time consuming, but there is significant potential in partnering with organisations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
0
13
0
1
Order By: Relevance
“…Natural barriers such as bodies of water and mountain ranges influence movement patterns and gene flow in wildlife populations 1 3 . Man-made physical barriers such as roads and fences similarly impact wildlife 4 7 . With the human population undergoing exponential growth and a continuing demand for ecotourism, enclosing wildlife in fenced areas is widespread in southern Africa 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Natural barriers such as bodies of water and mountain ranges influence movement patterns and gene flow in wildlife populations 1 3 . Man-made physical barriers such as roads and fences similarly impact wildlife 4 7 . With the human population undergoing exponential growth and a continuing demand for ecotourism, enclosing wildlife in fenced areas is widespread in southern Africa 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of South Africa found that roadkill reports from citizen scientists broadly identified the same hotspots and taxonomic groups in roadkill as reports from trained observers, although there was a slight bias in citizen scientist reporting towards more charismatic and easy-to-identify species [143]. Nevertheless, these data sources can help identify areas and taxa requiring further investigation and mitigation measures [144].…”
Section: Identifying Hotspotsmentioning
confidence: 97%
“…Roads that run through woodlands, forests, wetlands, and over drainage lines where animals are likely to move across the road, or the road disrupts any movement corridors [144,148], or where there is remnant habitat along the road [8,94,96] are high-risk for a large number of species in both mesic and arid environments. Season is also important; Servals (Leptailurus serval) were more frequently killed on the road in the dry season, and where there were adjacent wetlands in South Africa [144]. Similarly, kangaroos are killed more often on roads through open plains than other places [62].…”
Section: Spatial Effectsmentioning
confidence: 99%
“…The structure includes its materials, signs and markings. A considerable amount of research has been pursued on comparing AVCs in paved and unpaved roads [45,66,67]. The materials, themselves, do not typically affect the number of road kills in an area.…”
Section: Road Infrastructurementioning
confidence: 99%